Assessing the relationship between levator palpebrae superioris and thyroid-associated ophthalmopathy using the Dixon-T2WI sequence - Liu, Dan; Duan, Yongbo; Huang, Kai; Song, Cheng; Ouyang, Yufeng; Lin, Xiaoxin; Shen, Jie; Chen, Haixiong (Frontiers in Endocrinology, 2024)
The current clinical practice lacks sufficient objective indicators for evaluating thyroidassociated ophthalmopathy (TAO). This study aims to quantitatively assess TAO by evaluating levator palpebrae superioris (LPS) using Dixon-T2WI.The retrospective study included 231 eyes (119 patients) in TAO group and 78 eyes (39 volunteers) in normal group. Dixon-T2WI provided data on maximum thickness of LPS (LPS_T) and signal intensity ratio (LPS_SIR) between the muscle and ipsilateral brain white matter. TAO diagnosis and assessment of its activity and severity were quantitatively determined using LPS_T and LPS_SIR.In the TAO group, LPS_T and LPS_SIR were higher than those in the normal group (P < 2.2e-16). The upper lid retraction (ULR) ≥ 2 mm group exhibited higher LPS_T and LPS_SIR compared to the ULR < 2 mm and normal groups. Optimal diagnostic performance was achieved with AUC of 0.91 for LPS_T (cut-off: 1.505 mm) and 0.81 for LPS_SIR (cut-off: 1.170). LPS_T (P = 2.8e-07) and LPS_SIR (P = 3.9e-12) in the active phase were higher than in the inactive phase. LPS_T and LPS_SIR showed differences among the mild, moderate-to-severe, and sight-threatening groups (P < 0.05). ROC showed AUC of 0.70 for LPS_T (cut-off: 2.095 mm) in judging the active phase, and 0.78 for LPS_SIR (cut-off: 1.129). For judging moderate-to-severe and above, AUC was 0.76 for LPS_T (cut-off: 2.095 mm), and 0.78 for LPS_SIR (cut-off: 1.197).The maximum thickness and SIR of LPS provide imaging indicators for assisting in the diagnosis and quantitative evaluation of TAO.